Primary results from the Japanese Heart Failure and Sudden Cardiac Death Prevention Trial (HINODE) - Kazutaka Aonuma; Kenji Ando; Kengo Kusano; Toru Asai; Koichi Inoue; Yukihiro Inamura; Takanori Ikeda; Takeshi Mitsuhashi; Toyoaki Murohara; Nobuhiro Nishii; Akihiko Nogami; Wataru Shimizu; et al. (ESC Heart Failure)
Abstract Aims The HINODE study aimed to analyse rates of mortality, appropriately treated ventricular arrhythmias (VA), and heart failure in Japanese patients and compared with those in Western patients. Methods and results After treatment decisions following contemporary practice in Japan, patients were prospectively enrolled into four cohorts: (i) internal cardioverter‐defibrillator (ICD), (ii) cardiac resynchronization therapy (CRT) defibrillator (CRT‐D), (iii) standard medical therapy (‘non‐device’: ND), or (iv) pacing (indicated for CRT; received pacemaker or CRT pacing). Cohorts 1–3 required a left ventricular ejection fraction ≤35%, a history of heart failure, and a need for primary prevention of sudden cardiac death based on two to five previously identified risk factors. Endpoint outcomes were adjudicated by the independent committees. ICD and CRT‐D cohorts, considered as high‐voltage (HV) cohorts, were pooled for Kaplan–Meier analysis and propensity‐matched to Multicenter Automatic Defibrillator Implantation Trial‐Reduce Inappropriate Therapy (MADIT‐RIT) arm B and C patients. The study enrolled 354 patients followed for 19.6 ± 6.5 months, with a minimum of 12 months. Propensity‐matched HV cohorts showed comparable VA (P = 0.61) and mortality rates (P = 0.29) for HINODE and MADIT‐RIT. The ND cohort presented a high crossover rate to ICD therapy (6.1%, n = 7/115), and the CRT‐D cohort showed elevated mortality rates. The pacing cohort revealed that patients implanted with pacemakers had higher mortality (26.0%) than those with CRT‐Pacing (8.4%, P = 0.05). Conclusions The mortality and VA event rates of landmark trials are applicable to patients with primary prevention in Japan. Patients who did not receive guideline‐indicated CRT devices had poor outcomes.